Tracking Lone Wolf Terrorists - Rodger A. Bates (Journal of Public and Professional Sociology)
Terrorism takes many forms, and many advances in identifying and tracking terrorists have been made in the past few years. However, the rise of self-radicalized lone wolf terrorists is an increasing challenge, compounded by their different types and the social and political contexts in which their threats exist. These predators require multiple strategies to track and neutralize.